Model Prediksi Tingkat Kebisingan Pada Ruas Jalan Berdasarkan Volume Kendaraan dan Kecepatan di Bali - Bahtiar, Dani Ahmad Bahtiar; Ariawan , Putu; Iswara, I Komang Alit Purusa (Reinforcement Review in Civil Engineering Studies and Management, 2024)
This study focuses on Jalan Kerobokan, one of the busiest thoroughfares in Denpasar City, as a case study. The presence of diverse land uses, including schools, offices, and commercial centers, has led to a significant increase in traffic volume on Jalan Kerobokan, consequently resulting in elevated noise levels. The objective of this research is to analyze the relationship between traffic volume, speed, and noise levels on this road. A field survey was conducted to collect primary data, and multiple linear regression analysis was employed using SPSS software to model the relationship between these variables. The findings reveal that the highest traffic volume was recorded on Mondays, reaching 13,723 vehicles per hour. The average speed was measured at 31.09 km/h, while the noise level was found to be 84.755 dB(A). These results indicate that noise levels in the study area have exceeded the permissible limits. The mathematical model developed to represent the relationship between traffic volume, speed, and noise levels on Jalan Kerobokan is expressed as Y = 64.526 + 0.03X1 + 0.110X2 + 0.143X3 – 0.706X4, with an R-squared value of 0.244. This model suggests that traffic noise (Y) can be explained by the volume of motorcycles (X1), light vehicles (X2), heavy vehicles (X3), and traffic speed (X4).